Penggunaan Kata Cantik Dalam Majalah Wanita Femina, Kebaya Dan Kartini Edisi Oktober, November, Desember 2015 Dan Penerapannya Dalam Pelajaran Bahasa Di Sekolah - Raharjo, Is; Drs. Agus Budi Wahyudi, M.Hum, Drs. Agus Budi Wahyudi, M.Hum (2016)
Magazine is one form of media board composed based on words, phrases, clauses, and sentences made by the authors to attract readers. He wrote the language did not heed the arrangement grammatical sentence. The purpose of this study identifies a form of words and the function words that exist in the women's magazine Femina, Kebaya and Kartini edition of October, November, December 2015, and the application of lessons syntax in language lessons in school about the form of words, word form, and function in school. Sources of data in this study is a women's magazine Femina, Kebaya and Kartini 2015. In non-interactive data collection researchers used see and record. This type of research is qualitative descriptive. Researchers analyzed using basic techniques pilah decisive element (PUP) is sifting through the data concerned with the referent or reference. This study shows that a form of words that exist in the women's magazine Femina, Kebaya and Kartini edition of October, November, December 2015 consists of two forms of full words and word tasks. Femina, Kebaya and Kartini 2015 the dominant form full words for words that define overall pretty words have meaning and can stand alone. As in the full word: white, fashionable, exclusive, glamur, graceful, slender, charming, tender, sexy, beauty, clean, smooth, elegant and casual. Said task: and, besides, nan, from, with, forms a loan word as promotional products. Function words syntactically in a women's magazine Femina, Kebaya and Kartini edition of October, November, December 2015 serves as the said subject, predicate, object and information. Beautiful words as fillers function objects in the magazine Femina, Kebaya and Kartini 2015 more dominant. Form of words that exist in the magazines category of objects in the words: white, pretty, slim, sweet, graceful, beauty, charming, alluring, classy, lovely While on the subject in general the word beautiful is a complement of the subject to show the nature and identity. Implementation in language learning in school to help for the sisiwa terutaman on the level / high school level to be able to know the function and form of the subject, predicate, object, along with the description of the type of words contained in the sentence / discourse femina women's magazine, kebaya, and Kartini, 2015.